A History and Perspective of Non‐Fullerene Electron Acceptors for Organic Solar Cells. Issue 15 (14th January 2021) - Armin, Ardalan; Li, Wei; Sandberg, Oskar J.; Xiao, Zuo; Ding, Liming; Nelson, Jenny; Neher, Dieter; Vandewal, Koen; Shoaee, Safa; Wang, Tao; Ade, Harald; Heumüller, Thomas; et al.
Abstract: Organic solar cells are composed of electron donating and accepting organic semiconductors. Whilst a significant palette of donors has been developed over three decades, until recently only a small number of acceptors have proven capable of delivering high power conversion efficiencies. In particular the fullerenes have dominated the landscape. In this perspective, the emergence of a family of materials–the non‐fullerene acceptors (NFAs) is described. These have delivered a discontinuous advance in cell efficiencies, with the significant milestone of 20% now in sight. Intensive international efforts in synthetic chemistry have established clear design rules for molecular engineering enabling an ever‐expanding number of high efficiency candidates. However, these materials challenge the accepted wisdom of how organic solar cells work and force new thinking in areas such as morphology, charge generation and recombination. This perspective provides a historical context for the development of NFAs, and also addresses current thinking in these areas plus considers important manufacturability criteria. There is no doubt that the NFAs have propelled organic solar cell technology to the efficiencies necessary for a viable commercial technology–but how far can they be pushed, and will they also deliver on equally important metrics such as stability? Abstract : Organic photovoltaics have long promised low embodied energy, low cost solar power but have yet to make the commercial transition. Recent advances in efficiencies are potentially about to change this status‐quo, driven by a new class of semiconductors called the non‐fullerene electron acceptors. The emergence of these materials is reviewed, and perspectives provided as to future challenges and performance.